Implementasi Program Pemerintah dalam Menurunkan Angka Stunting: Studi Kasus Kecamatan Kota Selatan Kota Gorontalo - Suko, Mohammad Apriandi; Andi Inar Sahabat; Devika Rahayu Daud (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Stunting is a condition of impaired growth and development in children. It is a social issue that frequently occurs in communities, particularly in developing countries like Indonesia. This research aims to explain the implementation of stunting reduction programs conducted in the Kota Selatan District and to identify the inhibiting factors in the implementation of these programs in Gorontalo City. This study uses a qualitative research method with a descriptive approach, which allows for a more detailed understanding of the issues being examined.Based on the research findings, the stunting prevention and reduction program in the Kota Selatan District has been implemented properly. The program involved cross-sector collaboration, including the district head, the Gorontalo City Health Department, and the Kota Selatan Community Health Center. As of 2024, the number of children experiencing stunting in the district was recorded at 42. However, several factors were identified as problems with effective implementation. These include the lack of community awareness and participation, which hinders program effectiveness, the aid distribution that is not well-targeted and poor coordination and communication between institutions. These factors collectively slow down the stunting program's implementation process.